Impacts of photovoltaic connection on building load profile - Swe, Nwe Ni (2016)
Since over a long term, it is critical to improve the efficiency of power generation, transmission and distribution system. One of the missions of smart cities is to utilize more renewable distributed energy, which emits no greenhouse gas. Continuous combustion of carbon-fuels is harming potentiallyon every living things and environment worldwide. Managing of household energy consumption is the first step to achieve supply and demand balance more effectively. To reduce energy consumption and enhance energy utilization efficiency, load profile is very important to build the energy management system. This study is aimed to establish a bottom up mathematical model and simulate the load profile of residential and commercial buildings in Singapore using LabVIEW software. The solar irradiation power is analyzed to determine the solar PV output profile based on actual data recorded at Kallang, Singapore weather station. The two profiles are combined to determine the impact of PV on the total load profile. To reduce variation and increase predictability of supply and save cost, load shifting method is also employed in this project. Impacts of system cost will not be considered in this analysis. Improvement of energy consumption level, energy efficiency percentage with consideration of solar PV generation system will be studied in this project. This project has the advantage that it enables the consumers who are considering a solar PV installation to optimally manage the amount of energy needed in their daily lives at home and at work and analyze the potential impacts of PV system. Moreover, this project can help utilities maintaining balance between power supply and consumers demand and economic control through careful resource assessment and planning for future systems.